Step-by-step explanation:
Given that
![p(x)=3x+5,q(x)=4x-5](https://img.qammunity.org/2023/formulas/mathematics/college/pzzf3pnjgn49tuqvjhib6ceo7fiinzwor7.png)
Part A:
Find
![p(x)-q(x)](https://img.qammunity.org/2023/formulas/mathematics/high-school/xxo0xp99vmum8i4efvfsbkohydwpc17bvp.png)
By substituting the values, we will have
![\begin{gathered} p(x)-q(x)=3x+5-(4x-5) \\ p(x)-q(x)=3x+5-4x+5 \\ p(x)-q(x)=3x-4x+5+5 \\ p(x)-q(x)=-x+10 \\ p(x)-q(x)=10-x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/w01ib7sqfqa9aoaw87vevqnu17kc66f6qu.png)
Hence,
The final answer is
![p(x)-q(x)=10-x](https://img.qammunity.org/2023/formulas/mathematics/college/wgg0voxn0q461yg3gdnzhlloaiafbo8s1w.png)
Part B:
Find,
![p(x)+q(x)](https://img.qammunity.org/2023/formulas/mathematics/college/h5cflrct82nlbpjt3ahchv5s9jhtdlku9y.png)
By substituting the values, we will have
![\begin{gathered} p(x)+q(x) \\ p(x)+q(x)=3x+5+4x-5 \\ p(x)+q(x)=3x+4x+5-5 \\ p(x)+q(x)=7x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5xaqkgdom9usfkbwzwceyrylfhtmehrlc8.png)
Hence,
The final answer is
![p(x)+q(x)=7x](https://img.qammunity.org/2023/formulas/mathematics/college/wm3f0h2unvvswqfzw9ju0uf7p7pdikcbis.png)
Part C:
Find,
![p(x)q(x)](https://img.qammunity.org/2023/formulas/mathematics/college/u8a3qvzg5tnehdyrn7qqduud609zm065w3.png)
By substituting the values, we will have
![\begin{gathered} p(x)q(x)=(3x+5)(4x-5) \\ p(x)q(x)=3x(4x-5)+5(4x-5) \\ p(x)q(x)=12x^2-15x+20x-25 \\ p(x)q(x)=12x^2+5x-25 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/p69bmurdr23xdq1nsrvyiax81mx51s64nl.png)
Hence,
The final answer is
![p(x)q(x)=12x^(2)+5x-25](https://img.qammunity.org/2023/formulas/mathematics/college/pozbybpj0e5bazqo0lnvli8v9zbfh41f7y.png)